SEX WORKER STIGMA IN MAUPASSANT’S “BOULE DE SUIF” AND TIRTAWIRYA’S “CATATAN SEORANG PELACUR” - Linusia Marsih; Christine Saragih (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2021)
This study aims to reveal stigma toward sex worker depicted in two literary texts i. e. a short story entitled “Boule de Suif” by Guy de Maupassant, a French writer and a short story entitled “Catatan Seorang Pelacur” by Putu Arya Tirtawirya, an Indonesian writer. The two short stories are chosen for the reason that both works depect the life of a female sex worker. This study is designed as a descriptive qualitative study with sociological approach. The sociological approach is applied because this study looks at society’s views on female sex workers tht is reflected in the short stories. Moreover, theories of stigma are reviewed to support the analysis. The Analysis is focused on the sex worker stigma, the manifestation of stigmatization against sex workers, how the female sex worker in each short story responds to the stigmatization, and whether authors of the short stories affirm or criticize their society.